(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the clinical, paraclinical features and evaluate the treatment outcomes of tuberculous meningitis in patients with SLE at the National Lung Hospital from January 2017 to December 2022. Subjects and methods: A retrospective, cross-sectional descriptive study of 30 tuberculous meningitis patients with SLE from January 2017 to December 2022. Results: The median interval between the diagnosis SLE to the development of TB meningitis was 5,0 ± 4,8 (years). Main reasons for admission were fatigue (80,0%), headache (76,7%), and fever (70,0%). The treatment success rate was 68,0%, and the death rate was 16,0%. Factor associated with poor TB treatment was the occurrence of brain lesions on MRI scan (the difference was statistically significant with p < 0,05). Conclusion: It is necessary to think about and rule out the cause of tuberculous meningitis early in SLE patients with neurological symptoms to achieve good treatment results. The rate of treatment failure for tuberculosis meningitis in this group of patients remains high.